Voluntary guidelines for the design, construction and equipment of small fishing vessels 2005 (International Maritime Organization, 2006)
The purpose of these Guidelines is to provide information on the design, construction, and equipment of small fishing vessels with a view to promoting the safety of the vessel and safety and health of the crew. They are not intended as a substitute for national laws and regulations but may serve as a guide to those concerned with framing such national laws and regulations.